"But they were never only the master's tools": the use of photography in de-colonial praxis. (June 2017) - Pedri-Spade, Celeste
The majority of anthropological literature around photography of Indigenous peoples has privileged the actions, agency, and intent of the Western photographer. While one cannot ignore the significant colonizing influences that photographs have had on Indigenous peoples, one cannot presume that these individuals were solely the silenced subject or victim in a one-sided, inferior relationship with the camera and its operator. Recent scholarship is now re-examining the relationship Indigenous peoples have had with photography as a culturally productive technology since its development. In this article, I will address the role of photography in a global context as an object and a method of decolonization in two ways: (a) through archived collections of colonial photography and (b) in the production of contemporary photographs by peoples who experience contemporary colonialism. In both of these contexts, I will explore how various populations or communities with a colonial history use photography to confront ongoing legacies of colonialism, particularly in agendas aimed at repairing and reconfiguring relationships with self, family and kin, colonizer, community, and the natural world. Drawing on examples from several countries and locales, I will address the potentials and challenges of reframing Indigenous peoples' experience of, and relationship with, photography within the context of de-colonial praxis.